Structural and optical properties of Ba-doped CdO films prepared by SILAR method - (:unkn) unknown (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2014)
Nanostructure materials have opened a new discussion in the field of semiconductor device technology because material properties could be changed by changing the crystal morphology and size. In this article, Ba doped CdO films were prepared by SILAR method. The crystal morphology, structure and optical properties of the films were characterized by scanning electron microscopy, X-ray diffraction and ultraviolet-visible spectroscopy, respectively. From the SEM analysis it is seen that Ba-doping concentration affects the shapes of the nanostructures. XRD analysis showed that the films have poly-crystalline structures. The room temperature UV-vis analysis showed that the optical band gap of the CdO films was firstly decreased then increased with the increasing barium doping concentration. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Nanostructures; Barium; CdO; SILAR; OXIDE THIN-FILMS; ELECTRICAL-PROPERTIES; PHYSICAL-PROPERTIES; TEMPERATURE; DEPOSITION